PENATALAKSANAAN SEPSIS AKI PADA PASIEN MULTIPLE MYELOMA DENGAN HIPERKALSEMIA BERAT - Agus Sumedi (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2018)
This case report talking about a female 56 yo with Multiple Myeloma (MM) suffer from Pneumonia and Acute Kidney Injury (AKI). MM is haematology cancer produce free light chain that impair renal tubulus, cause anemia, bone lesion and hypercalcemia. This patient came to hospital withsevere pneumonia, acute kidney injury andsevere hypercalcemia. In intensive care unit supported by mechanical ventilation, diuretic, antibiotics administration,haemodialysis,vasoactive agents, bisphosphonat and others.The acitenobacter baumanni was identified from sputum culture and then developed become multidrugs resistant leading to septic syock and multi organs dysfunction and death in two weeks.